ARTERIAL STIFNESS AND SYMPATHETIC OVERDRIVE IN HYPERTENSIVE PATIENTS WITH ANGINA AND NON-OBSTRUCTIVE CORONARY ARTERY DISEASE. (June 2022) - Sakalidis, Athanasios; Dimitriadis, Kyriakos; Dri, Eirini; Soulaidopoulos, Stergios; Manta, Eleni; Leontsinis, Ioannis; Mantzouranis, Emmanouil; Fragoulis, Christos; Konstantinidis, Dimitrios; Tsioufis, Konstantinos
Abstract : Objective: Existing data support that hypertension is related to sympathetic overdrive and arterial stiffness. Non-obstructive coronary artery disease (CAD) is frequent among hypertensive patients with angina. Nowadays, there are scarce evidence on the role of sympathetic nervous system (SNS) in the above population. The aim of this preliminary analysis of our study was to assess whether hypertensive patients with angina and non-obstructive CAD, hypertensives without angina and normotensive controls are characterized by different level of SNS activation and arterial stifness. Design and method: We studied 13 hypertensive patients with angina and non-obstructive CAD in coronary angiography [9 females, mean age: 61.2 ± 9.9 years, office blood pressure (BP): 159/96 ± 14/10 mmHg], 16 treated hypertensive patients without angina (9 females, mean age: 59.5 ± 7.5 years, office BP:142/88 mmHg) and 11 normotensive controls (8 females, mean age: 51.8 ± 11 years, BP:125/87 mmHg). In all participants, sympathetic drive was assessed by muscle sympathetic nerve activity (MSNA) estimated by microneurography and arterial stiffness, measured with heart rate-corrected aortic augmentation index (Aix@75), calculated by analyzing the ambulatory blood pressure monitoring (ABPM) waveforms. Results: Hypertensives with angina and non-obstructive CAD (n = 13) compared to hypertensive patients without angina (n = 16) and normotensive individuals (n = 11) exhibited higher levels of MSNA (59.6 ± 6.6 vs 43 ± 8.4 vs 45 ± 9.5 bursts per minute, respectively; p < 0.01 for all) and 24-h BP (146/85 ± 18/11 vs 141/83 ± 7/10 vs 125/81 ± 7/6 mmHg, respectively; p < 0.001 for all). Hypertensives with and without angina did not differ regarding renal function based on eGFR (p = NS). Moreover, there were no differences in left ventricular mass index, total cholesterol and low-density lipoprotein between hypertensive patients with and without angina and no gender related effects on MSNA and Aix@75 (p = NS). Furthermore, patients with angina and non-obstructive CAD patients compared to hypertensives without angina were characterized by increased levels of Aix@75 (36.13 ± 7.4 vs 22.5 ± 11.7, p < 0.05). Conclusions: Patients with hypertension and non-obstructive CAD are characterized by higher MSNA and increased Aix levels compared to hypertensives without angina and normotensive controls. These preliminary results suggest that therapies targeting sympathetic overdrive and vascular stiffening could provide additional clinical benefit in this special category of hypertensive patients.